Translation and Validation of Marathi Version of Oral Health Impact Profile?14, a Measure of Oral Health?Related Quality of Life - Doibale, Pradyumna; Deogade, Suryakant; Khalikar, Arun; Wankhede, Sattyam; Kapadia, Archit; Dutta, Vinay (Indian Journal of Community Health, 2022)
Background: A quality of life (QoL) assessment tool needs to be translated and validated in the language of the participants to whom it is administered. Therefore, the oral health impact profile-14 (OHIP-14) scale, developed originally in English, has been translated into different languages like Hindi, Gujrati, etc. The Marathi version of OHIP-14 will be useful to assess in regions where the Marathi language is prominently spoken. Thus, the present study was carried out to translate and validate the Marathi version of the OHIP-14 instrument to measure the oral health-related quality of life. Aims & Objectives: To translate and validate the English Version of the OHIP-14 instrument in the Marathi Language. Materials and Methods: This was a descriptive cross-sectional study in which 128 participants were selected through a convenient sampling method. The English version of the OHIP-14 was translated using the forward-backward translation technique, and participants were given English and the Marathi versions of the OHIP-14 questionnaire. The filled questionnaires were subjected to statistical analysis. Result: The difference in mean scores was not statistically significant(p=0.828). Pearson’s correlation coefficient test was 0.999, suggesting that the translated Marathi version is highly correlated with the original English version. Conclusion: The Marathi version of OHIP-14 is a valid, and reliable instrument for assessing QoL among the population who speak Marathi.